ANALYSIS OF EMPLOYMENT CONTRACTS IN ISLAMIC ECONOMIC PERSPECTIVE - Nurul Rafiqoh Lubis; Fadhillah Insani; Fatma Wati; Isnaini Harahap (Proceeding International Seminar of Islamic Studies, 2023)
Contracts are often a problem for workers. Which usually often occurs friction between parties from employers and workers due to its subordinative nature. The weak position of workers in work agreements means that many workers do not get their rights as they should as stipulated in Law no. 13 of 2003 regarding employment. For this reason, it is necessary to analyze how the work contract is based on an Islamic view. This study uses library research methods using reference sources from books and various journals and other scientific works which are certainly relevant to the theme. The results of this study are work contracts (outsourcing) according to Islam are the same as ijarah. This means that the relationship between the outsourcing company and its workers is established in the form of an ijarah. Because, the four schools of thought, Hanafiah, Syafi'iyah, Malikiyah, and Hanafiyah define the concept of ijarah by making the property of something beneficial for a certain time with a replacement.